Project Evaluation Based On Sharia Construction Management and Green Building Principles - Agung Sedayu (IPTEK Journal of Proceedings Series, 2017)
This current Indonesia has many problems in project development that caused many conflicts. Housing projects problem for the community needs to get the handling and solving. The habits for project developers to obtain maximum profit but much harm to users need to be repaired and straightened. The purpose of this research to evaluate the quality of services procurement projects in Griya Amorf Sawojajar Malang, East Java with an overview of the principles of Islamic Sharia Management and Sustainable and Green Building. This research use Islamic Sharia caused this principles can be used in many problems that has relation with social-culture aspects. The principles will be adapted to cosnrtuction management. At this current, many project construction cause more complex environmental damage. The destruction in enviromnetal can be solved and evaluated by using green building principles. Green building is derivied from building sustainable produce bulding that environmental friendly. This research methods are Importance Performance Analysis (IPA) and Quality Function Deployment (QFD). The IPA results obtained 12 factors with the highest score of importance is the construction process on time schedule of the project. The QFD results obtained 17 technical response with the highest score is the service with sharia system: payment, contract, agreement, and information clearly and honestly.